PEMBERDAYAAN IBU PKK DESA GUWANG DALAM PENGGUNAAN OVITRAP BERBAHAN ALAMI UNTUK MEMBERANTAS VEKTOR PENYAKIT DEMAM BERDARAH DENGUE - putu indah budiapsari (Universitas Lancang Kuning, 2023)
Sourced from data obtained at the Sukawati 1 Health Center, the highest dengue hemorrhagic fever case in the working area of the Sukawati 1 Health Center is Guwang Village. In 2020, 64 cases of dengue hemorrhagic fever were found in Guwang Village. This service aims to empower the community to increase motivation to live clean and healthy to play an important role in controlling dengue hemorrhagic fever cases. The method used in this service is counseling and training for PKK mothers in Guwang village with a minimum number of participants of 30 people. The location of this activity is at Banjar Sakih, Guwang Village, which will be held in September 2022. The results of this activity are expected to increase the knowledge and skills of PKK women in using and making ovitrap made from natural ingredients as measured through pretest and posttest. The result of this service is an increase in the knowledge and attitude of PKK mothers in eradicating mosquito nests, using ovitrap made from natural ingredients.